Effect of mediastinal radiotherapy on 30 day mortality after cardiac surgery - M. N. Sorkomov; S. I. Babenko; D. A. Titov; A. S. Sachkov; M. I. Terekhov; R. A. Serov; R. M. Muratov (Вестник трансплантологии и искусственных органов)
Late complications affecting the cardiovascular system depend on the extent of the capture of cardiac structures in the radiation field and the cumulative dose of exposure. They are characterized by polymorphism in clinical manifestations. Objective: to identify the predictors influencing in-hospital mortality (IHM) in order to optimize the treatment of patients with radiation-induced heart disease. Materials and methods. This is a single-patient cohort study that was retrospective from 2004 to 2018 and prospective from 2018. Death after 30 days following heart valve surgery (HVS) under artificial circulation was taken as the end point of the study. The study included 86 patients (mean age 59 ± 13 years, 81.4% female) who underwent HVS. They were split into 2 groups (extensive, tangential) depending on the cause of cancer. Results. In the postoperative period, the group with extensive irradiation had statistically significant differences in the need for prolonged ventilation, OR 5.17 (CI 95% 1.7–15.7), more frequent exudative pleurisy OR 3.4 (CI 95% 1.1–10.8), and acute renal failure OR 1.2 (CI 95% 1.05–1.37). Regardless of postoperative complications, the length of hospital stay did not differ statistically across the groups, with a median of 10.5 (CI 7.25:16.75) vs. 11 (CI 9:15.25) days, respectively. Overall IHM was 14 (16.27%) patients. Multiple organ failure (MOF) was the cause of death in 9 cases. Multivariate analysis revealed that extensive irradiation for lymphogranulomatosis increased IHM risk by 5.099 times, and an increase in the EuroSCORE II score by every «1» increased IHM risk by 1.19 times. Conclusion. Patients with post-radiation damage to heart valves and coronary arteries with a history of tangential irradiation can be successfully operated on. Extensive irradiation in anamnesis is associated with a high risk of heart failure and MOF in the early postoperative period.